Fish Microbiological Analysis and Identification of Bacterial Germs (The International Journal for Scientific Research, 2025)
The occurrence of microbiological contamination in marine environments is a potential consequence of the discharge of sewage from human or animal sources into coastal water. The contamination of marine environments by microorganisms represents a significant global concern, given the adverse impact of such contamination on aquatic life, particularly fish. Leaping Mullet samples were collected from Zuwara around  the port  of Zuwara,  results showed that  the Colonies are rosé cream-colored colonies Gram-negative, Shigella spp 3*102 cfu/g. Samples collected from the marine environnement in Sabratha Sea surrounded by sewage water where Kocuria Varians Yersinia Pseudotuberculosis isolated from Leaping Mullet, Pagellus erythrinus and   Sphyraena barracuda 3*103, 5*103  and 8.*103 cfu/g, respectively. Conclusion was identifying the microbiological contamination on the marine environment of the Sabratha and Zuwara Sea.
Keywords: Sewage Water; Fish Contamination; Bacterial Identification